The use of autologous skeletal muscle-derived cells as a sling in the treatment of stress-induced urinary incontinence: An experimental study in dogs - Wadie, Bassem S.; Aamer, Haytham G.; Khater, Sherry M.; Gabr, Mahmoud M. (Frontiers in Urology, 2023)
Purpose This is an experimental preclinical study testing the applicability of autologous skeletal muscle-derived cells as a treatment of SUI in a canine model. Methods Ten mongrel dogs were included in this study. Skeletal muscle was harvested for biopsy in 4 dogs. One month later, incontinence was induced in 8 dogs through urethrolysis. Biopsied muscle cells were incubated and expanded for 8 weeks. Muscle-derived cells were collected and covered with a polyglycolic acid (PGA) scaffold immersed in culture medium and coated with Matrigel to be used as a sling, which was placed suburethrally in 8 dogs; 4 had cell seeding, and 4 had scaffolds only. Urethral pressure (UP) measurements were performed at baseline and 2 & 6 weeks after sling insertion. The urethra was harvested 4 weeks after sling insertion for histopathology. Results One month, a statistically significant increase of mean urethral pressure values compared to baseline was observed in all dogs with a scaffold inserted. The increase ranged from 5 to 40 cmH2O. Histopathology showed significant periurethral proliferation of skeletal muscles in 4 dogs with cell-seeded scaffolds. These levels were the maximum levels in dogs # 1 & 2. This was not the case in the 4 dogs that had slings only. Conclusion Based on the outcome of this preliminary experience, the use of skeletal muscle-seeded PGA scaffolds seems to be an easy and reproducible procedure which preserves histological differentiation and integrity in a canine model